The road warrior ; Mad Max beyond Thunderdome [videorecording (DVD)] - Miller, George, III, 1945-; Ogilvie, George, 1931-2020; Gibson, Mel; Turner, Tina (Distributed by Warner Bros. Home Entertainment, 2017)
The road warrior: In the post-nuclear outback of Australia, a battle is waged by a tiny band of civilized survivors and a group of barbarians over a precious cache of gasoline. Mad Max beyond Thunderdome: Once again, Mad Max stands alone against the barbarians of a post-nuclear age. This time, Max defends the future--a group of abandoned children--and enters the gladiatorial maces-and-chainsaws combat inside Thunderdome arena.